ROS-related antibacterial mechanism and Ca-enhanced osteogenetic property of Ca-doped magnetite nanoparticles. Issue 15 (1st August 2022) - Ning, P.; Liu, C.C.; Ma, X.; Mao, G.W.; Luo, D.F.; Wang, Y.J.; Hou, Y.F.; Fu, T.
Abstract: Calcium doped magnetite nanoparticles were synthesized by the chemical co-precipitation method for osteogenetic and antibacterial applications in biomedical fields. The prepared powders are composed of Fe3 O4 and calcium ferrite, but Fe2 O3 ·H2 O (i.e. FeOOH) and CaCO3 are also detected at high calcium content. Aggregated spherical nanoparticles (diameter 12–15 nm) are observed by SEM and TEM, but clusters of needle-like nanorods appear especially for samples with high calcium content. The particles have much larger hydrodynamic diameter values (170–250 nm) and positive surface charge. Magnetic properties of the samples generally decrease with calcium content, including saturation magnetization, coercivity and residual magnetization. Antibacterial tests by plate counting, TEM observation and intracellular reactive oxygen species (ROS) assay suggest that the samples with high calcium content have better bactericidal activity, and the main mechanisms include the physical mutilation effect of nanoparticles and the oxidative stress induced in the bacteria. Cell tests using MC3T3-E1 cells show that the tested samples have good cytocompatibility, and the alkaline phosphatase (ALP) activity is dose-dependent for the nanoparticles. The developed Ca-doped magnetite nanoparticles with high magnetism, good antibacterial and osteogenetic properties would find potential application in different biomedical fields.